Implementasi pendidikan karakter mandiri dalam P5 Gaya Hidup Berkelajutan kelas X di SMA Negeri 1 Parung - Muhamad Robi; Illiyin; Tatu Khabibah (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2023)
This journal discusses independent character education embedded in P5 with the theme of a sustainable lifestyle. The method used is descriptive qualitative. This journal shows the process of implementing independent character education carried out by 5 class X teachers using interviews through Gform. The results in this journal show that class X teachers instill independent character education for class X students in P5 Sustainable Lifestyles at SMA Negeri 1 Parung.